ANALYSIS OF LIVABLE STREET AT HOS. COKROAMINOTO STREET CORRIDOR AS A PUBLIC SPACE IN PONOROGO REGENCY - Hilba Yoga Pratama; Agung Budi Sardjono (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2023)
Abstract : Public space in an urban area has an important role to improve the quality of life for the general public. Public space in the form of street corridors is a very important element in the infrastructure system of a region or city. A street corridor in an urban area does not only function as a mobility lane for vehicles, but can also function as a forum for community activities, and can create a unique identity for an area. The Hos. Cokroaminoto street corridor in Ponorogo Regency is one of the street that is often used by the Ponorogo Regency Government to hold several cultural events, in this street corridor the general public also carries out social and commercial activities. The purpose of this study is to explain the quality of the Hos. Cokroaminoto street corridor as a public space which is reviewed from several aspects in the form of physical and non-physical aspects, as well as activities that are created by identifying their linkages with existing facilities. The research method uses descriptive qualitative, by presenting an overview regarding the real condition of the street corridor, and findings about the existing conditions in an effort to create a